2017
DOI: 10.1021/acs.jafc.7b01735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Muscle-Specific Oxidative Stress on Cytochrome c Release and Oxidation–Reduction Potential Properties

Abstract: Mitochondria play a significant role in beef color. However, the role of oxidative stress in cytochrome c release and mitochondrial degradation is not clear. The objective was to determine the effects of display time on cytochrome c content and oxidation-reduction potential (ORP) of beef longissimus lumborum (LL) and psoas major (PM) muscles. PM discolored by day 3 compared with LL. On day 0, mitochondrial content and mitochondrial oxygen consumption were greater in PM than LL. However, mitochondrial content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…Previous studies in normal pH muscles demonstrated that MRA decreased in LL and PM muscles across display and LL exhibited greater MRA than PM, which is in agreement with our results [7,34]. Similarly, Ke et al (2017) reported that LL had greater MRA than PM, and MRA in PM drastically decreased during the first three days of display [36]. In support, English et al…”
Section: A C C E P T E Dsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies in normal pH muscles demonstrated that MRA decreased in LL and PM muscles across display and LL exhibited greater MRA than PM, which is in agreement with our results [7,34]. Similarly, Ke et al (2017) reported that LL had greater MRA than PM, and MRA in PM drastically decreased during the first three days of display [36]. In support, English et al…”
Section: A C C E P T E Dsupporting
confidence: 93%
“…Compared with DC-LL and Np-PM, Np-LL showed lower OC (P < 0.05), while remarkably, the PM of DC beef had higher (P < 0.05) OC than the LL of Np beef. Previous studies have demonstrated that OC decreased in muscle with increasing days of display [5,36]. The decreased OC could be explained by the reduction in the functional ability of the mitochondria due to extended post-mortem time and depleted substrates [37].…”
Section: Oxygen Consumptionmentioning
confidence: 91%
“…More specifically, with less efficient antioxidant system in postmortem muscles, greater oxygen consumption by PM mitochondria can generate reactive oxygen species that can initiate mitochondrial degradation. A recent study reported that cytochrome c content increased in sarcoplasm of PM than LL during display (Ke et al., ), which indicates mitochondrial damage.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, more stable mitochondrial activity, specifically mitochondrial MRA, in the LL may contribute to its color stability. Decrease in mitochondrial MRA of PM, in part, can be attributed to greater degeneration than LL mitochondria during display (Ke et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Mohan et al (2010) reported that the differences in cytochrome c oxidase activity among the three muscles (LL > psoas major > semitendinosus) corresponded well with metmyoglobin reducing activity and colour stability differences exhibited by these muscles. Ke et al (2017) reported approximately 1.8-fold difference in mitochondrial content between beef psoas major and LL muscles and suggested that greater oxygen consumption rate may possibly be detrimental to colour stability. The low abundance of cytochrome c oxidase in vitamin E-fed beef observed in the present study may decrease oxygen consumption rate, similar to the low oxygen consumption rates in the muscles with low levels of mitochondria.…”
Section: Figurementioning
confidence: 99%